An integrated assessment of the Good Environmental Status of Mediterranean Marine Protected Areas. (1st March 2022) - Fraschetti, Simonetta; Fabbrizzi, Erika; Tamburello, Laura; Uyarra, María C.; Micheli, Fiorenza; Sala, Enric; Pipitone, Carlo; Badalamenti, Fabio; Bevilacqua, Stanislao; Boada, Jordi; Cebrian, Emma; Ceccherelli, Giulia; et al.
Abstract: Local, regional and global targets have been set to halt marine biodiversity loss. Europe has set its own policy targets to achieve Good Environmental Status (GES) of marine ecosystems by implementing the Marine Strategy Framework Directive (MSFD) across member states. We combined an extensive dataset across five Mediterranean ecoregions including 26 Marine Protected Areas (MPAs), their reference unprotected areas, and a no-trawl case study. Our aim was to assess if MPAs reach GES, if their effects are local or can be detected at ecoregion level or up to a Mediterranean scale, and which are the ecosystem components driving GES achievement. This was undertaken by using the analytical tool NEAT (Nested Environmental status Assessment Tool), which allows an integrated assessment of the status of marine systems. We adopted an ecosystem approach by integrating data from several ecosystem components: the seagrass Posidonia oceanica, macroalgae, sea urchins and fish. Thresholds to define the GES were set by dedicated workshops and literature review. In the Western Mediterranean, most MPAs are in good/high status, with P. oceanica and fish driving this result within MPAs. However, GES is achieved only at a local level, and the Mediterranean Sea, as a whole, results in a moderate environmental status. Macroalgal forests are overall in bad condition, confirming their status at risk. The results are significantly affected by the assumption that discrete observations over small spatial scales are representative of the total extension investigated. This calls for large-scale, dedicated assessments to realistically detect environmental status changes under different conditions. Understanding MPAs effectiveness in reaching GES is crucial to assess their role as sentinel observatories of marine systems. MPAs and trawling bans can locally contribute to the attainment of GES and to the fulfillment of the MSFD objectives. Building confidence in setting thresholds between GES and non-GES, investing in long-term monitoring, increasing the spatial extent of sampling areas, rethinking and broadening the scope of complementary tools of protection (e.g., Natura 2000 Sites), are indicated as solutions to ameliorate the status of the basin. Highlights: A comparative assessment of environmental health across the Mediterranean Sea. Overall, the basin found in a generally moderate environmental status. Good/high status reached only in the Western Mediterranean Marine Protected Areas. Seagrasses and fish drive these results. Macroalgae are overall in bad conditions. Marine Protected Areas are crucial as sentinel observatories of marine systems.